Intranasal oxytocin increases covert attention to positive social cues - Domes, Gregor; Sibold, M.; Schulze, L.; Lischke, Alexander; Herpertz, Sabine; Heinrichs, M. (Psychological medicine, 2013)
BackgroundThe neuropeptide oxytocin (OT) has positive effects on the processing of emotional stimuli such as facial expressions. To date, research has focused primarily on conditions of overt visual attention.MethodWe investigated whether a single intranasal dose of OT (24 IU) would modulate the allocation of attentional resources towards positive and negative facial expressions using a dot-probe paradigm in a sample of 69 healthy men. Attentional capacity for these facial cues was limited by presentation time (100 or 500 ms). In addition, we controlled for overt visual attention by recording eye movements using a remote eye tracker.ResultsReaction times (RTs) in the dot-probe paradigm revealed a pronounced shift of attention towards happy facial expressions presented for 100 ms after OT administration, whereas there were no OT-induced effects for longer presentation times (500 ms). The results could not be attributed to modulations of overt visual attention as no substance effects on gazes towards the facial target were observed.ConclusionsThe results suggest that OT increased covert attention to happy faces, thereby supporting the hypothesis that OT modulates early attentional processes that might promote prosocial behavior.